Anticancer Properties of Phyllanthus emblica (Indian Gooseberry). (9th June 2015) - Zhao, Tiejun; Sun, Qiang; Marques, Maud; Witcher, Michael
Abstract : There is a wealth of information emanating from both in vitro and in vivo studies indicating fruit extract of the Phyllanthus emblica tree, commonly referred to as Indian Gooseberries, has potent anticancer properties. The bioactivity in this extract is thought to be principally mediated by polyphenols, especially tannins and flavonoids. It remains unclear how polyphenols from Phyllanthus emblica can incorporate both cancer-preventative and antitumor properties. The antioxidant function of Phyllanthus emblica can account for some of the anticancer activity, but clearly other mechanisms are equally important. Herein, we provide a brief overview of the evidence supporting anticancer activity of Indian Gooseberry extracts, suggest possible mechanisms for these actions, and provide future directions that might be taken to translate these findings clinically.